2011
DOI: 10.1088/0957-0233/22/7/075202
|View full text |Cite
|
Sign up to set email alerts
|

Observability analysis for model-based fault detection and sensor selection in induction motors

Abstract: Sensors in different types and configurations provide information on the dynamics of a system. For a specific task, the question is whether measurements have enough information or whether the sensor configuration can be changed to improve the performance or to reduce costs. Observability analysis may answer the questions. This paper presents a general algorithm of nonlinear observability analysis with application to model-based diagnostics and sensor selection in three-phase induction motors. A bond graph mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Then, the modified stator resistance estimation is performed offline applying (21) and (22) using these current and voltage data in (23) and (24).…”
Section: Modified Stator Resistance Alternative Estimation Methods Fromentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the modified stator resistance estimation is performed offline applying (21) and (22) using these current and voltage data in (23) and (24).…”
Section: Modified Stator Resistance Alternative Estimation Methods Fromentioning
confidence: 99%
“…The simulation tests have been performed with a 0.5-HP 2-pole IM. The rated values and parameters for the IM are presented in Table 1 [24]. The IM was simulated as a dynamic model based on the state-space equations, with inserted mechanical losses [1].…”
Section: Tested Induction Motormentioning
confidence: 99%
“…The observability matrix O , bold-italicOtrue(mnnormal*ntrue)=bold-italicqbold-italicx =[]|Lf0hx1Lf0hxnLfn1hx1Lfn1hxn, is defined as the Jacobian of the Lie derivative vector q . For calculation of this Jacobian, a numerical differentiation method in complex domain was implemented which has the advantage of being indifferent to the scale of truex as described previously . The analytical computation of the Jacobian matrix would be impractical and time consuming for most applications because of the existence of highly nonlinear functions in the Lie derivative vector.…”
Section: Methodsmentioning
confidence: 99%
“…For calculation of this Jacobian, a numerical differentiation method in complex domain was implemented which has the advantage of being indifferent to the scale of x * as described previously. 20,21 The analytical computation of the Jacobian matrix would be impractical and time consuming for most applications because of the existence of highly nonlinear functions in the Lie derivative vector. The nonlinear system is observable if the rank of the observability matrix, O, is equal to the number of state variables, n. For enhancing the A 0 : growing biomass; A 1 : nongrowing biomass; PEN: penicillin concentration; A 2 : vacuoles; A 3 : degenerated biomass; A 4 : autolyzed biomass; r e : rate of extension; r b : rate of branching; r p : rate of penicillin production; r h : rate of penicillin hydrolysis; r d [1][2][3][4] : rates of differentiation of biomass from one type to another.…”
Section: Observability Analysismentioning
confidence: 99%
“…Nakhaeinejad et al [4] suggested a similar approach not only for analysis of the faults, but also for defining a guideline for model-based sensor selection for induction motors. Among all of the abovementioned methods, the condition number is more common and is frequently used in the literature [1], [5], [6].…”
Section: Introductionmentioning
confidence: 99%